Micro, Small, and Medium Sized Enterprises’ (MSMEs) Participation in Peacebuilding: Motivators and Barriers - Dr. Mark P. Doblas; Dr. Laurence P.Bazan; Tiburcio P.Ybanez (International Journal of Engineering and Management Research, 2019)
The academic literature has provided substantial amount of suggestions on broad concepts of business fostering peace in the community just by doing its operations properly. However, many could contend if these businesses could be urged to perform larger roles as agents for peace. Consequently, the desire to have businesses, particularly the Micro, Small and Medium Enterprise (MSME), to act as key players in peacebuilding largely depends on the understanding of what could motivate them in acting such key role and what could possibly hinder them in doing the same. Thus, this study is an exploration of the motivators and challenges of MSMEs in acting as main agents for peacebuilding. The study utilized a descriptive research design involving thirty conveniently sampled MSMEs in Butuan City, Philippines. A researcher-made questionnaire was used as data gathering tool. A multivariate analysis was done to analyse the effect of participation and perceived risk in the identified motivators and barriers. The results of the study revealed thatinternal motivators are the greatest motivators in acting for peace.In addition, financial and political reasons are strong barriers for MSMEs to participate in peacebuilding. Finally, the study found that Level of Perceived Risk and Participation significantly affects the type of motivators and barriers MSMEs face in peacebuilding movements.